Anesthetics inhibit phosphorylation of the ribosomal protein S6 in mouse cultured cortical cells and developing brain - Friese, Matthew B.; Gujral, Taranjit S.; Palanisamy, Arvind; Hemmer, Brittany; Culley, Deborah J.; Crosby, Gregory (Frontiers in Aging Neuroscience, 2023)
The development and maintenance of neural circuits is highly sensitive to neural activity. General anesthetics have profound effects on neural activity and, as such, there is concern that these agents may alter cellular integrity and interfere with brain wiring, such as when exposure occurs during the vulnerable period of brain development. Under those conditions, exposure to anesthetics in clinical use today causes changes in synaptic strength and number, widespread apoptosis, and long-lasting cognitive impairment in a variety of animal models. Remarkably, most anesthetics produce these effects despite having differing receptor mechanisms of action. Based on this observation, we hypothesized that anesthetic agents mediate these effects by inducing a shared signaling pathway. To test this hypothesis, we exposed cultured cortical cells to propofol, etomidate, or dexmedetomidine and assessed the protein levels of dozens of signaling molecules and post-translational modifications using reverse phase protein arrays. As anesthetics cause profound changes in neural activity, we performed separate control experiments to alter neural activity with non-anesthetics. The results indicate that all the anesthetic agents tested reduce phosphorylation of the ribosomal protein S6, an important member of the mTOR signaling pathway. We then tested whether this effect occurs in vivo by anesthetizing postnatal day 7 animals with sevoflurane, an agent used commonly in children, and found a comparable decrease in S6 phosphorylation by Western blotting. These results suggest that a reduction in S6 phosphorylation and subsequent suppression of the mTOR pathway may be a common and novel signaling event that mediates the impact of general anesthetics on neural circuit development.